Measuring Learning Outcomes of Integer Arithmetic Operations through E-MoBil Media in Primary Education - Yanuar Puji Rahayu; Ariefa Efianingrum; Unik Ambar Wati (Universitas Pendidikan Ganesha, 2024)
The ability of Indonesian students to solve math exam questions, particularly in integer arithmetic operations, remains a challenge, indicating incomplete mastery of mathematical concepts. This study aims to test the construct validity and reliability of a learning outcome scale for integer arithmetic operations in AKM numeracy for fifth-grade elementary school students through the development of E-MoBil media based on Flip PDF Professional. The development method used follows Borg & Gall's model but focuses on nine key steps: information gathering, planning, initial product development, preliminary field testing, initial product revision, main field testing, product revision, operational field testing, and final product revision. The primary data collection instrument was a questionnaire, analyzed using confirmatory factor analysis with LISREL 8.80 software. The results show that the developed learning outcome scale meets the criteria for model fit, convergent validity, discriminant validity, and construct reliability. These findings demonstrate that the E-MoBil media developed using Flip PDF Professional is effective in enhancing students' understanding of integer arithmetic operations and is suitable for use in learning activities. This study provides significant contributions to the development of technology-based learning evaluation tools to improve elementary students' numeracy literacy.